Opóźnienia w funkcjonowaniu językowym jako wczesny symptom zaburzeń w rozwoju dziecka1 - Leszka, Justyna (Kultura-Społeczeństwo-Edukacja, 2021)
Human linguistic development is constitutionally conditioned and is achieved through contact with adult language users. All children follow the same rules and stages in the development of speech. The knowledge of their course and consequences enables early recognition of deviations from the norm, which may be delayed speech development or a symptom of other, often serious developmental disorders. The analysis of the research results shows that the most common reason for parents’ seeking diagnosis and therapeutic support is an incorrect linguistic functioning of the child. Diagnostic procedures often end with the diagnosis of other developmental disorders in which linguistic retardation was an early symptom. Therefore, it is legitimate to increase social knowledge and sensitivity of parents and specialists in monitoring the linguistic development of children under 3 years of age.